The growth and meat quality of Siamese catfish fed different level of protein - Purnomo, Novieanto; Utomo, Nur Bambang Priyo; Azwar, Zafril Imran (Jurnal Akuakultur Indonesia, 2015)
ABSTRACT This study was to evaluate growth performance and meat quality of Siamese catfish Pangasianodon hypophthalmus fed on commercial diets with different protein levels. Fish with average initial body weight of 33,61 g were reared in hapa (2×2×1 m3) at density of 30 ind/hapa. Fish were hand-fed with experimental diet to satiety twice daily for 60 days. Experimental design was set in completely randomized design. Each treatment was done in triplicates. Experimental diets were a commercial diet to contain four differennt levels of protein; i.e. diet A (18%), diet B (23%), diet C (28%), and diet D (32%). Specific growth rate (SGR), feed conversion ratio (FCR), protein (RP) and lipid (RL) retention, hepatosomatic index (HSI), lipid and glycogen content of liver, protein and lipid content of meat, edible portion, and fillet textural were calculated. The results of the experiment showed that the highest weight gain and SGR, lowest FCR and meat protein were obtained in the group of fish fed 23%–32% protein diets. In conclusion, 23% protein diets gave the best growth performance and meat quality of Siamese catfish. Keywords : growth performance, meat quality, commercial diet, Pangasianodon hypophthalmus  ABSTRAK Penelitian ini bertujuan untuk mengevaluasi kinerja pertumbuhan dan kualitas daging ikan patin siam Pangasianodon hypophthalmus yang diberi pakan komersial dengan kandungan protein berbeda. Ikan patin yang digunakan dengan bobot awal 33,61 g ditebar sebanyak 30 ekor/hapa ukuran 2×1×1 m3 dan ikan diberi pakan percobaan dua kali sehari secara at satiation selama 60 hari. Penelitian ini didesain dalam rancangan acak lengkap dengan empat perlakuan dan tiga ulangan. Pakan yang digunakan adalah pakan komersial dengan empat kandungan protein yang berbeda: pakan A (18%), pakan B (23%), pakan C (28%), dan pakan D (32%). Parameter uji pada penelitian ini adalah laju pertumbuhan spesifik (SGR), rasio konversi pakan (FCR), retensi protein (RP), retensi lemak (RL), indeks hepatosomatik (HSI), lemak dan glikogen hati, protein dan lemak daging, serta tekstur daging. Hasil penelitian menunjukan bahwa penambahan bobot tubuh, SGR tertinggi, FCR terendah, dan protein daging diperoleh pada perlakuan protein pakan 23%–32%. Hasil penelitian ini menunjukkan bahwa perlakuan protein pakan 23% memberikan kinerja pertumbuhan dan kualitas daging ikan terbaik. Kata kunci: kinerja pertumbuhan, kualitas daging, pakan komersial, Pangasianodon hypophthalmus